Character Skills and Patience to Promote Resilience in Children - Education in Primary Schools After Pandemic - Guarcello, Emanuela (European Journal of Social Science Education and Research, 2024)
The proposal of the education of character skills in childhood has and still represents an authoritative experience within the educational landscape with particular regard to the school environment. If the proposal of character education has been so widely accepted to date, how can it be a valid support for the school even after the pandemic? In order to represent a valid support to all intents and purposes, should it maintain the traits that have distinguished it up to now or should it change in some respects? In particular, what skills should then be promoted by character education in schools after the pandemic? Starting from these problematic spaces and in order to work on a reconstruction of possible answers to the questions raised, the present contribution is articulated around three main reflexive nests: the education of character with particular regard to the proposal of character skills by James Josef Heckman; the relationship between conscientiousness (central to the discourses on character) and patience, an educational proposal centered on patience’s skills that should be promoted through character education in schools, especially at primary level, after the pandemic.
Keywords: primary school, character, skills, conscientiousness, patience, resilience, waiting, indecision